APPLICATION OF BUILDING INFORMATION MODELLING (BIM) FOR SAFETY MANAGEMENT (SM) DURING THE OPERATION AND MAINTENANCE (O&M) PHASE IN BUILDINGS IN KAZAKHSTAN - Kopeyev, Dastan (Nazarbayev University School of Engineering and Digital Sciences, 2022)
Safety management is one of the key concerns of the construction objects industry. Building information modeling enables the creation of a digital built environment of the building. It could also be applied for early safety issues identification and safety management throughout the construction project lifecycle. Currently, BIM usage for building O&M phase safety still has little attention. There are different studies evaluating its general efficiency in early safety risks identification and usage of the BIM model for safety management during building operation and maintenance. Kazakhstan is currently in the important stage of BIM adoption, but no studies observe BIM application for Kazakhstani building O&M safety.
Keywords: type of access: open access